Corrigendum to “The million-year evolution of the glacial trimline in the southernmost Ellsworth Mountains, Antarctica” [Earth and Planetary Science Letters 469 (2017) 42–52] - Sugden, David E.; Hein, Andrew S.; Woodward, John; Marrero, Shasta M.; Rodés, Ángel; Dunning, Stuart A.; Stuart, Finlay M.; Freeman, Stewart P.H.T.; Winter, Kate; Westoby, Matthew J. (Earth and Planetary Science Letters, 2018)
This corrigendum fixes an error in the reporting of 21Ne concentrations, which affected one batch of samples that included thebedrock depth profile from which cosmogenic 10Be, 26Al and 21Newere modelled to constrain the age and exposure history of thePatriot Hills (Fig. 8 in the manuscript). Re-modelling the cosmogenic nuclide data using the corrected 21Ne data yields an apparent exposure age of 3.5–5.1 Ma. This corrects an age published as2.1–2.6 Ma in Sugden et al. (2017), and reinforces the conclusion ofthe original paper that the glacial trimline is pre-Quaternary andthat the climatic conditions necessary for its erosion last occurredin the Mid-Miocene.The revised Supplementary Table 1 has been updated with corrected 21Ne concentrations and consistent reporting of 10Be concentrations. The revised Supplementary Table 2 has been updatedwith 21Ne exposure ages for the affected batch of samples. Below,we describe the revised model results and present a revised Fig. 8.Tables 1 and 2, Fig. 8 and its caption replace those in the original paper. The corrections reinforce the conclusions of the originalpaper.